Strategi Pemasaran Jasa Pembuatan Jajanan Tradisional Gerai PKK Dan UMKM Desa Dasan Borok Kecamatan Suralaga Kabupaten Lombok Timur - Muhammad, Farhana; Aini, Qurratul; Riswanto, Agus; Rozikin, Muh (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2025)
Marketing strategy is an important component in the world economics, where it is one of the determinants of a person’s success in carrying out economic activities. Strategy plays an important role in supporting the sustainability of economic life in the fields of marketing, business or interprise. Marketing strategy can also be said to be a way to obtain big profits if the strategy can be executed well and correctly.    This research was descriptive in nature using a qualitative approach. The data collection methods used were observation, interviews, and documentation. The research result show that the marketing strategy used by the PKK and  UMKM outlets still uses ordinary and minimal strategies, such as relying solely on lip to lip, coustomers who come directly to the outlet, using cell phones, and even social media the only media used is still facebook. Even though there are many strategies that can be used to get even greater benefits, such as collaboration weith scholl agencies, offices and health centere, using social media, which now have many types, as well as trying print media that can be usedexpand the outlet network.